"Ferula assa-foetida L" or "Foeniculum vulgare"? Which one is more effective in the management of polycystic ovarian syndrome? A randomized, placebo controlled, triple-blinded - Fatemeh Ghavi; Fatemeh Shakeri; Somayeh Abdolahian (Mashhad University of Medical Sciences, 2023)
Objective: There are few evaluation about the effects of Fennel and Ferula on human polycystic ovary syndrome (PCOS). The goals of this study were to evaluate and compare the effectiveness of two medicinal plants of the Apiaceae family (Fennel and Ferula) in management of PCOS.Materials and Methods: The sample size was 47 participants with PCOS who were randomly divided into 3 groups. The Ferula assa-foetida L group received 100 mg of Ferula (n=14), the Foeniculum vulgare group received 46 mg of Fennel (n=15), and the placebo group received placebo twice daily for 3 months (n=14).Results: Before the intervention, there were no significant differences between groups in terms of clinical parameters, endometrial thickness, or ovarian volume. After the interventions, the number of ovarian follicles was decreased in the Ferula and Fennel groups as compared to the placebo group (p<0.05). The number of ovarian follicles in both ovaries in the Ferula and Fennel group decreased and this decrease was significant in the right side as compared to placebo group. Our findings showed significant changes in dehydroepiandrosterone sulfate (DEHAS) and thyroid-stimulating hormone (TSH) levels after the intervention (p<0.03) between the Ferula and Placebo groups.Conclusion: Since use of Ferula could make significant changes in TSH and DEHAS levels and decrease the number of right and left ovarian follicles compared to Fennel and placebo, it can be concluded that this herbal medicine is more effective than Fennel in managing PCOS.